Understanding cerebral L‐lysine metabolism: the role of L‐pipecolate metabolism in Gcdh‐deficient mice as a model for glutaric aciduria type I. Issue 2 (12th September 2014) - Posset, Roland; Opp, Silvana; Struys, Eduard A.; Völkl, Alfred; Mohr, Heribert; Hoffmann, Georg F.; Kölker, Stefan; Sauer, Sven W.; Okun, Jürgen G.
Abstract: Inherited deficiencies of the L‐lysine catabolic pathway cause glutaric aciduria type I and pyridoxine‐dependent epilepsy. Dietary modulation of cerebral L‐lysine metabolism is thought to be an important therapeutic intervention for these diseases. To better understand cerebral L‐lysine degradation, we studied in mice the two known catabolic routes — pipecolate and saccharopine pathways — using labeled stable L‐lysine and brain peroxisomes purified according to a newly established protocol. Experiments with labeled stable L‐lysine show that cerebral L‐pipecolate is generated along two pathways: i) a minor proportion retrograde after ε‐deamination of L‐lysine along the saccharopine pathway, and ii) a major proportion anterograde after α‐deamination of L‐lysine along the pipecolate pathway. In line with these findings, we observed only little production of saccharopine in the murine brain. L‐pipecolate oxidation was only detectable in brain peroxisomes, but L‐pipecolate oxidase activity was low (7 ± 2μU/mg protein). In conclusion, L‐pipecolate is a major degradation product from L‐lysine in murine brain generated by α‐deamination of this amino acid.